Risk of Epilepsy After Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Investigators at the Institute of Neurology, London, and at other centers in the UK and the Netherlands conducted a prospective follow-up of 181 infants from the onset of febrile seizures for a median of 21.6 years, to estimate the long-term risk of developing epilepsy.